Compton's encyclopedia and fact-index - F.E. Compton Company ([Chicago] : F. E. Compton Co., 1978)
Alphabetically arranged articles in each of the twenty-six volumes are supplemented by brief factual entries on additional topics in that volume's index
8 COPIES
1
Keywords: Encyclopedias and dictionaries; Encyclopedias and dictionaries